ONE ON ONE.COM: A STRATEGY IN ENHANCING THE COMPUTER LITERACY OF EMPOWERMENT TECHNOLOGY STUDENTS - Ong, Rubijane (International Journal of Business, Law, and Education, 2022)
This action research study is conducted to determine the effect of one-on-one Tutorials with performance task sheets as an intervention for the low performance of students in Isabela School of Arts and Trades Senior High School taking up Empowerment Technology Subject. Thirty-seven students consented to participate in the study. It was found out that the intervention has a medium positive effect in improving the students' computer skills. Thus, the intervention is encouraging to be utilized in the teaching and learning process. The method and procedure of the research used is descriptive comparative design in this study wherein the data were generated from the pre and post-test results of the respondents in their Empowerment of Technology subject for the first semester 2019 – 2020, specifically in learning Competency Advanced Spreadsheet skills.